Thermal image building inspection for heat loss diagnosis. (September 2019) - Preda, A.; Scurtu, I. C.
Abstract: Thermal imaging inspection for building applications it is powerful and non invasive method for monitoring and diagnosing the condition of buildings. With a thermal imaging camera you can identify problems early. This method allows us to check and correct issues before becoming more serious and more costly. By this method, we can exemplify the heat loss through the surface of the building. Thermal imaging consists of scanning the building with infrared, using a special camera. The radiated heat leads to a temperature variation on the surface of the building element in which is embedded. This method, corroborated with the calculation of heat loss, provides a technical and economical solution for the problem of thermal discomfort in the building.